2020
DOI: 10.21203/rs.3.rs-48366/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Opportunistic Pathogen Sphaeropsis Sapinea is Found to be one of the Most Abundant Fungi in Symptomless and Diseased Scots Pine in Central-Europe

Abstract: Background: The opportunistic and latent pathogen Sphaeropsis sapinea is one of the most important forest pathogens on pine. The fungus may cause Diplodia tip blight on several coniferous trees and disease symptoms come visible when trees are weakened by stress, usually related to injuries and drought. This project compares the mycobiome of healthy and diseased Scots pines. Twigs were sampled in June and September 2018 in a German forest stand with varying health status of the sampled Scots pines. Growth of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 65 publications
1
19
1
Order By: Relevance
“…No S. sapinea could be detected from the tested seedlings prior to the experiments, whereas the other fungal strains used for the greenhouseinfections were found to be present. We concluded that these species belong to the naturally observed Scots pine endophyte community (Blumenstein et al, 2020;Bußkamp et al, 2020).…”
Section: Pre-colonization Of the Trees With Fungal Communitymentioning
confidence: 78%
See 4 more Smart Citations
“…No S. sapinea could be detected from the tested seedlings prior to the experiments, whereas the other fungal strains used for the greenhouseinfections were found to be present. We concluded that these species belong to the naturally observed Scots pine endophyte community (Blumenstein et al, 2020;Bußkamp et al, 2020).…”
Section: Pre-colonization Of the Trees With Fungal Communitymentioning
confidence: 78%
“…The fungal strains chosen are regularly isolated from Scots pine tips in German forests according to Bußkamp et al (2020). Origin and locations of the strains are described in Blumenstein et al (2020). One strain (Didymellaceae sp., NW-FVA ID 5756) originated from a sample of the nursery pine plants (see section "Pre-experiment Detection of Endophytes Including Sphaeropsis sapinea in Plant Material") that were used in this study for the antagonism assay.…”
Section: Fungal Material: Isolates From Scots Pine Tipsmentioning
confidence: 99%
See 3 more Smart Citations